A survey of libraries of Bible schools belonging to the Philippine Association of Bible and Theological Schools (PABATS) - Siodora, Anastacia V. (Institute of Library Science, University of the Philippines Diliman, 1977)
This is a survey of twenty Bible school libraries which are member of the Philippine Association of Bible and Theological Schools. The libraries surveyed fall under three categories, according to the level of training offered, namely: Bible institutes, Bible colleges and theological schools. A brief history of Bible schools is traced from its inception in America to its introduction in the Philippines. The study includes all aspects of Bible school libraries: their administration and organization, personnel, library resources, services rendered, and facilties.